1994
DOI: 10.1161/01.cir.89.1.302
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and angiographic results of transluminal extraction coronary atherectomy in saphenous vein bypass grafts.

Abstract: In patients with stenoses in saphenous vein bypass grafts, TEC atherectomy is limited by the frequent need for adjunctive balloon angioplasty to achieve adequate lumen enlargement and to manage TEC atherectomy-induced complications. Although the incidence of serious clinical complications is similar to that of other percutaneous interventions in vein grafts, there is a high incidence of restenosis and late vessel occlusion. Prospective randomized studies are needed to determine the best revascularization strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(40 citation statements)
references
References 32 publications
2
35
0
3
Order By: Relevance
“…10 -12 Repeat bypass operation is associated with a significant risk for the patient, 13 leaving percutaneous angioplasty as the best alternative for many patients. As a result, new devices have been developed to limit distal embolization; these include the intracoronary administration of urokinase, 14 extraction coronary atherectomy, 15 directional coronary atherectomy, 16 laser angioplasty, 17,18 ultrasound thrombolysis, 19 and AngioJet rapid thrombectomy. 20,21 Unfortunately, these techniques have generally failed to reduce distal embolization adequately.…”
Section: Discussionmentioning
confidence: 99%
“…10 -12 Repeat bypass operation is associated with a significant risk for the patient, 13 leaving percutaneous angioplasty as the best alternative for many patients. As a result, new devices have been developed to limit distal embolization; these include the intracoronary administration of urokinase, 14 extraction coronary atherectomy, 15 directional coronary atherectomy, 16 laser angioplasty, 17,18 ultrasound thrombolysis, 19 and AngioJet rapid thrombectomy. 20,21 Unfortunately, these techniques have generally failed to reduce distal embolization adequately.…”
Section: Discussionmentioning
confidence: 99%
“…The reported primary success rate is adequate and is associated with a relatively low complication rate [9,10,11]. Safian et al [12] reported procedural success in 84% of 158 saphenous vein graft lesions in 146 consecutive patients. Serious clinical complications included 2.0% death, 0.7% emergency bypass surgery, 2% Q-wave myocardial infarction, 2.7% non-Q-wave infarction, and 6.1% vascular injury requiring surgical repair and/or blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…The technique uses numerical integration to calculate the time that would give an equivalent thermal dose at a reference temperature under different temperature profiles. The reference temperature of 43˚C has been chosen since this is the standard temperature used as a reference [21]. For any temperature profile the dose can be found by …”
Section: Estimation Of Thermal Dosementioning
confidence: 99%
“…In advanced cases, atherosclerosis treatment may require special surgical procedures such as Balloon Angioplasty [9][10][11][12], Balloon Angioplasty and Stenting [13][14][15], Cutting Balloon [16][17][18][19][20][21], Atherectomy [22,23], Surgical Bypass [24,25] and Endarterectomy [26,27] to open an artery and improve blood flow.…”
Section: Introductionmentioning
confidence: 99%